Surgical Management of Gingival Recession Using Free Gingival Autograft: A Case Report - Neupane, Manisha; Humagain, Manoj; Subba, Mahima; Lamichhane, Simant; Dawadi, Asmita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Gingival recession leads to dentinal hypersensitivity, aesthetic problems, root caries, cervical abrasion and difficulty in oral hygiene maintenance. Managing gingival recession often is a great challenge for practitioners. Different surgical techniques have been advocated for root coverage like free soft tissue graft procedures free gingival graft and sub-epithelial connective tissue graft, pedicle soft tissue graft rotational flap and flap advancement, pouch and tunnel technique and guided tissue regeneration. This case report displays use of free gingival graft for management of patient of age 22 years with Miller’s Class I recession defect in lower left mandibular central incisor.